Проблеми та перспективи розвитку гірськолижного туризму в Україні (на прикладі Івано-Франківської області) - Романова, Катерина Євгеніївна; Romanova, K. (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Роботу присвячено дослідженню проблем та перспектив розвитку гірськолижного туризму в Івано-Франківській області. Розглянуто визначення поняття «гірськолижний туризм». Досліджено соціально-економічну сутність гірськолижного туризму. Вивчено закордонний досвід реалізації проєктів гірськолижного туризму. Проаналізовано сучасний стан розвитку гірськолижного туризму в Україні. Охарактеризовано ресурсний потенціал гірськолижного туризму в Івано-франківської області. Виявлено перспективи розвитку гірськолижного туризму в регіоні.

The paper is devoted to the analysis of challenges and development prospects of alpine ski tourism in the Ivano-Frankivsk region of Ukraine. The study provides a conceptual definition of "alpine ski tourism" and examines its socio-economic nature. International experience in implementing alpine ski tourism projects is reviewed and assessed. The current state of alpine ski tourism in Ukraine is analyzed, with particular attention to trends and development dynamics. The natural, infrastructural, and institutional resources of alpine ski tourism in the Ivano-Frankivsk region are characterized in detail. The research identifies key opportunities for sustainable tourism development in the region and offers practical recommendations to enhance its competitiveness in the national and international tourism markets.
Challenges and prospects for the development of Alpine ski tourism in Ukraine (the case of Ivano-Frankivsk region)
Керівник: Панова Ірина Олексіївна, кандидат економічних наук, доцент кафедри світової політики, дипломатії та туристичного бізнесу
Keywords: SOCIAL SCIENCES::Other social sciences; гіррськолижний туризм; туристичні ресурси; туристична інфраструктура; Івано-Франківська область; соціально-економічний розвиток; туристичний потенціал; регіональна політика; alpine ski tourism; tourism resources; tourism infrastructure; Ivano-Frankivsk region; socio-economic development; tourism potential; regional policy